Tumor-Penetrating Microparticles for Intraperitoneal Therapy of Ovarian Cancer - Lu, Ze; Tsai, Max; Lu, Dan; Wang, Jie; Wientjes, M. Guillaume; Au, Jessie L.-S. (The Journal of pharmacology and experimental therapeutics, 2008)
Intraperitoneal chemotherapy prolongs survival of ovarian cancer patients, but its utility is limited by treatment-related complications and inadequate drug penetration in larger tumors. Previous intraperitoneal therapy used the paclitaxel/Cremophor EL (polyethoxylated castor oil) formulation designed for intravenous use. The present report describes the development of paclitaxel-loaded microparticles designed for intraperitoneal treatment (referred to as tumor-penetrating microparticles or TPM). Evaluation of TPM was performed using intraperitoneal metastatic, human ovarian SKOV3 xenograft tumor models in mice. TPM were retained in the peritoneal cavity and adhered to tumor surface. TPM consisted of two biocompatible and biodegradable polymeric components with different drug release rates; one component released the drug load rapidly to induce tumor priming, whereas the second component provided sustained drug release. Tumor priming, by expanding interstitial space, promoted transport and penetration of particulates in tumors. These combined features resulted in the following advantages over paclitaxel/Cremophor EL: greater tumor targeting (16-times higher and more sustained concentration in omental tumors), lower toxicity to intestinal crypts and less body weight loss, greater therapeutic efficacy (longer survival and higher cure rate), and greater convenience (less frequent dosing). TPM may overcome the toxicities and compliance-related problems that have limited the utility of intraperitoneal therapy.